IMPROVING SPEAKING SKILL BY USING YOUTUBE - Vera Dila; Gaya Tridinanti (Didascein : Journal of English Education, 2021)
English is an international language used to communicate and interact with other people in the world. It has the widest range of any language spoken today. English is found in many fields for social communication, such as politics, business, science, technology, entertainment even it is the most language used in the internet. It means that English is the global language of spoken communication for many activities. The objective of this study was to find out whether or not there was any significant improvement on speaking skill by using YouTube at SMA Methodist 2 Palembang. This study used pre-experimental method that was used quantitative approach with one group pretest and posttest design. There were 24 students taken as the sample by using purposive sampling technique as an experimental group. The class was X. MIA1. In collecting the data, speaking test was used as the technique. The result of paired sample t-test of speaking skill showed that the value of t-obtained was 10.837 at the significance level 0.000 with degree of freedom was 23. It means that the result of the data showed that there was significant improvement on speaking skill students The students were interested in joining the class and more creative during teaching and learning process.Keywords: YouTube, speaking skill, descriptive text